2012
DOI: 10.1124/jpet.112.193201
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Dopamine D2-Like Receptor Function in a Rodent Model of Schizophrenia

Abstract: Based on the observation that antipsychotic medications display antagonist properties at dopamine D2-like receptors, aberrant dopamine signaling has been proposed to underlie psychosis in patients with schizophrenia. Thus, it is not surprising that considerable research has been devoted to understanding the mechanisms involved in the antipsychotic action of these compounds. It is important to note that the majority of these studies have been performed in "normal" experimental animals. Given that these animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
(66 reference statements)
4
16
0
Order By: Relevance
“…(B,C)]. It should be noted that dopamine D4 receptor expression was below the limits of detection, consistent with our previous observations (Perez and Lodge, ). Furthermore, NAc expression of TH (adult: NAc: 8.05 ± 0.43 cf.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…(B,C)]. It should be noted that dopamine D4 receptor expression was below the limits of detection, consistent with our previous observations (Perez and Lodge, ). Furthermore, NAc expression of TH (adult: NAc: 8.05 ± 0.43 cf.…”
Section: Resultssupporting
confidence: 90%
“…To examine dopamine‐related molecular mechanisms that may underlie the different behavioral responses between preadolescent and adult rats, quantitative RT‐PCR was performed using probes for the dopamine D1, D2, D3, D4, D5 receptors, as well as the DAT, tyrosine hydroxylase and dopamine receptor signaling molecules RGS2, RGS9 and GIRK2. We have previously reported that adult, MAM‐treated rats display significant increases in D3 receptor expression throughout the NAc (Perez and Lodge, ). Here we demonstrate, that preadolescent rats do not display significant differences in the expression of a number of dopaminergic markers throughout either the NAc or VTA [three‐way ANOVA; F 1,180(Region) = 0.256, F 1,180(Age) = 2.032, F 8,180(Gene) = 1.738, F 1,180(Region × Age) = 0.580, F 8,180(Region × Gene) = 0.395, F 8,180(Age × Gene) = 1.054, F 8,180(Region × Age × Gene) = 0.518, all p > 0.05; Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Consistent with the pharmacological studies detailed above, rats with selective vHipp PV knockdown display increases in the number of spontaneously active VTA dopamine neurons, without overt changes in firing rate or bursting pattern. This neurophysiological phenotype is consistent with that observed in rodent models of schizophrenia, such as the MAM-treated rat (Lodge and Grace, 2007; Perez and Lodge, 2012, 2013; Perez et al, 2013). Interestingly, while the increase in dopamine neuron activity is qualitatively similar to that of the MAM-treated rat, it appears to be of a smaller magnitude.…”
Section: Discussionsupporting
confidence: 87%
“…This can be directly examined in rodent models by recording the electrophysiological activity of midbrain dopamine neurons (Lodge and Grace, 2007; Perez and Lodge, 2012, 2013). Such studies have suggested that the increase in dopamine system function is associated with changes in the number of spontaneously active neurons in the absence of changes in firing rate or bursting pattern (Lodge and Grace, 2007; Perez and Lodge, 2012, 2013). Under control conditions, it is thought that about 50% of the midbrain dopamine neurons are quiescent due to a tonic GABAergic drive from the ventral pallidum (VP) (Grace et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The dopaminergic neurotransmitter system (DAS) has been implicated in the etiopathogenesis of schizophrenia since antipsychotics were found to reduce psychotic symptoms by blocking D2/D3 dopamine receptors [1].Findings from both animal [2] and human in vivo and postmortem studies [3 -4] have provided further evidence for structural and functional abnormalities in the DAS in schizophrenia. Since its first description, it is an ongoing reformulation of the dopamine hypothesis of schizophrenia [5].…”
Section: Introductionmentioning
confidence: 99%